Extrahepatic malignancies in a liver transplant recipient from a living related donor - I. Yu. Kolyshev; S. E. Voskanyan; M. V. Shabalin; A. I. Artemyev; V. S. Rudakov; A. P. Maltseva; A. N. Bashkov; V. E. Syutkin; K. K. Gubarev; D. S. Svetlakova; M. V. Popov; A. I. Sushkov; et al. (Трансплантология (Москва))
Background. Cancer occurring in recipients of living donor liver transplantation may be characterized by a progressive course requiring an immediate specialized treatment initiation and adjustment of immunosuppression regimen. Aim. To specify the malignancy development mechanisms and risk factors in the recipients of living donor liver transplantation. Material and methods: 275 living donor liver transplantations were made in Burnasyan Federal Medical Biophysical Center of FMBA from 2010 to 2020. Forty two (15.27 %) patients underwent surgery for hepatocellular carcinoma. The median time to the onset of malignancy development was estimated. The incidence of malignancy in general population and in recipients of living donor liver transplantation was compared. Results. The development of neoplastic lesion was registered in 9 cases (3.27%). Malignances were detected in 8 cases (2.90%). Median time to the onset of malignancy development was 48 months. 1, 3, and 5 year overall survival rates were 97%, 96%, 94%;respectively; 1, 3, and 5 year survival rates after transplantation for hepatocellular cancer were 97%, 91%, 91% respectively. Survival rate of patients with De-novo malignancy was 90%. Conclusion. Recipients of living donor liver transplantation have an increased risk of malignancy development that requires a close long-term follow-up.